Coronary Artery Disease and Coronary Artery Bypass Grafting at the Time of Lung Transplantation Do Not Impact Overall Survival. Issue 10 (October 2019) - Halloran, Kieran; Hirji, Alim; Li, David; Jackson, Kathy; Kapasi, Ali; Meyer, Steve; Mullen, John; Lien, Dale; Weinkauf, Justin
Abstract : Background: Coronary artery disease (CAD) is common in lung transplant candidates and may require revascularization before or at the time of their transplant. We reviewed the survival of lung transplant recipients with CAD requiring surgical intervention (CAD-coronary artery bypass grafting [CABG]) and those who did not (CAD-NoCABG) at the time of transplant, compared to a cohort with no CAD (NoCAD). Methods: We conducted a retrospective cohort study of adult patients transplanted in our program between 2004 and 2013. Our primary outcome was the association between 3-way CAD status (CAD-CABG, CAD-NoCABG, NoCAD) and overall retransplant-free survival via proportional hazards modeling, adjusting for age, gender, and transplant indication. Secondary endpoints included 1-year survival, survival by Kaplan-Meier analysis, duration of ventilation, intensive care unit stay, and hospitalization. Results: A total of 333 patients underwent transplant during the study timeframe. A total of 24 (7%) had CAD requiring CABG, 82 (25%) had CAD not requiring CABG, and the remaining 227 had no CAD. The 3-way CAD status was not associated with overall retransplant-free survival after adjustment for age, gender, and transplant indication. Duration of mechanical ventilation, intensive care unit stay and hospitalization were longer in both CAD groups compared with the NoCAD group. Conclusions: CAD status does not impact overall retransplant-free survival, despite greater perioperative complexity. Prospective studies comparing treatment strategies in these patient groups are warranted. Abstract : Supplemental Digital Content is available in the text.